The Internet of Things and its anticipated influence on digital service quality: A survey at the Central Library of the University of Babylon - Omaima Hameed Aladilee (Universitas Negeri Malang, 2026)
This study examines the anticipated influence of Internet of Things (IoT) applications on digital service quality in the Central Library of the University of Babylon. The research focuses on IoT as an independent variable represented by technical infrastructure, integration with digital services, user experience, and security and privacy. Digital service quality is treated as the dependent variable and is represented by impact on beneficiaries, information control, the library physical and digital environment, and smart interaction. A survey method was used to collect responses from a purposive sample of 209 library beneficiaries. The questionnaire was designed using a five-point Likert scale, and the data were analyzed through descriptive statistics, reliability analysis, confirmatory factor analysis, correlation, and linear regression using SPSS and AMOS. The findings indicate that IoT has a statistically significant positive effect on digital service quality, explaining 46% of the variance. Technical infrastructure, integration with digital services, and user experience significantly contribute to enhancing service quality, whereas security and privacy, although rated highly by users, did not show a statistically significant direct effect in the regression model. The study recommends strengthening technical infrastructure, improving information control systems, integrating digital services, and developing smart interaction features to support user-centered digital transformation in university libraries.